Professional and pedagogical orientation as a determinant of becoming a professional engineer future teacher - Максименко, Ірина (Pedagogy of Higher and Secondary Education, 2014)
Maksymenko I. G. Professional and pedagogical orientation as a determinant of becoming a professional engineer future teacher. The article discloses the essence of professional pedagogical orientation, describes semantic, procedural and motivational components of its structure, dynamics of index’s reduction in satisfaction of professional selection, stages of personal development, criteria and levels of development. The article covers the signification of professional development in the future of engineer-teache.